Altering standard admission order sets to promote clinical laboratory stewardship: a cohort quality improvement study. Issue 10 (9th May 2019) - Leis, Benjamin; Frost, Andrew; Bryce, Rhonda; Lyon, Andrew W; Coverett, Kelly
Abstract : Background: Careful design of preprinted order sets is needed to prevent medical overuse. Recent work suggests that removing a single checkbox from an order set changes physicians' clinical decision-making. Local problem: During a 2-month period, our coronary care unit (CCU) ordered almost eight times as many serum thyroid-stimulating hormone (TSH) tests as our neighbouring intensive care unit, many without a reasonable clinical basis. We postulated that we could reduce inappropriate testing and improve clinical laboratory stewardship by removing the TSH checkbox from the CCU admission order set. Methods: After we retrospectively evaluated CCU TSH ordering before intervention, the checkbox was removed from the CCU admission order set. Twelve weeks later, we commenced a prospective 2-month assessment of TSH testing and clinical sequelae of thyroid disease among all CCU admissions. If clinical indications were absent or testing had occurred within 6 weeks, TSH requests were labelled as 'inappropriate'. Results: Physician ordering and, specifically, inappropriate ordering decreased substantially after the intervention. In 2016 among physician-ordered TSH tests, 60.6% (66/109) were inappropriate; in 2017 this decreased to 20% (2/10, p=0.01). Overall, the net effect of checkbox removal saw the decrease in TSH testing without clinical indication outweigh an increase in missed testing where indications appear to exist. Conclusions: Provision of an optional checkbox for a laboratory test in an admission order set can promote overuse of laboratory resources . Simple removal of a checkbox may dramatically change test ordering patterns and promote clinical laboratory stewardship. Given our reliance on order sets, particularly by trainees, changes to order sets must be cautious to assure guideline-directed care is maintained.